Investigating the Local Buckling of Rectangular Corrugated Plates - Vahid Abdolvahab (Salehan Institute of Higher Education, 2016)
With advances in technology in recent years, the use of orthotropic materials to exclude the mechanical deficiencies of homogeneous plates has increased. Sinusoidal corrugated plates are known as orthotropic plates, as a result of changes in their mechanical properties in two orthogonal directions. Since use of corrugated plates, in particular steel shear walls instead of flat steel plates, has increased, the present study investigated local buckling of sinusoidal corrugated plates under uniform uniaxial loading on the transverse edges of the plate (vertical loading on the sinusoidal wave of corrugated plates), using the Galerkin method. This method is very powerful with regard to solving differential equations, and directly uses these equations in the process of problem-solving. Finally, the results obtained for the critical buckling load of sinusoidal corrugated metal plates and the results relating to the metal homogeneous flat plates were compared using the same supporting conditions and loading.